Spectroscopic parameters for ozone and its isotopes: recent measurements, outstanding issues, and prospects for improvements to HITRAN; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 82, № 1-4 - Rinsland C. P.; Flaud J. M.; Perrin A.; Birk M.; Wagner G.; Goldman A.; Barbe A.; Tyuterev Vl. G.; Smith M.A.H.; Devi V. M.; Benner D. C.; Schreier F.; et al. (2003, 2003)
Title screen